2023
DOI: 10.1007/s40820-023-01181-8
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Doped Nickel Sulfide for Electro-Upgrading Polyethylene Terephthalate into Valuable Chemicals and Hydrogen Fuel

Zhijie Chen,
Renji Zheng,
Teng Bao
et al.

Abstract: Electro-upcycling of plastic waste into value-added chemicals/fuels is an attractive and sustainable way for plastic waste management. Recently, electrocatalytically converting polyethylene terephthalate (PET) into formate and hydrogen has aroused great interest, while developing low-cost catalysts with high efficiency and selectivity for the central ethylene glycol (PET monomer) oxidation reaction (EGOR) remains a challenge. Herein, a high-performance nickel sulfide catalyst for plastic waste electro-upcyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Heteroatom doping can alter the electronic structure of metal chalcogenides 142 and thus alleviate the intrinsic activity for urea electrolysis. 143 Liu et al found that the doping of Fe into Ni 3 S 2 could modify the coordination structure of Ni atoms and further optimize the adsorption energies of reaction intermediates on Ni sites.…”
Section: Applications Of Bifunctional Electrocatalysts For Urea Elect...mentioning
confidence: 99%
“…Heteroatom doping can alter the electronic structure of metal chalcogenides 142 and thus alleviate the intrinsic activity for urea electrolysis. 143 Liu et al found that the doping of Fe into Ni 3 S 2 could modify the coordination structure of Ni atoms and further optimize the adsorption energies of reaction intermediates on Ni sites.…”
Section: Applications Of Bifunctional Electrocatalysts For Urea Elect...mentioning
confidence: 99%
“…10,11 Another approach is chemical recycling of PET at the molecular level, which encompasses the depolymerization of PET waste into virgin monomers or value-added chemicals. 12–15 For example, a library of excellent research studies has upcycled PET waste into specific key intermediates for the synthesis of functional polymers such as polyurethane, 16 polyester, 17–19 polyimine, 20 epoxy, 21 acrylic and alkyd resins, 22 as well as small molecules such as p -xylene, 23 formate salts, 24 and dichloroethane. 25 However, owing to deep depolymerization at the molecular level, chemical recycling faces difficulty in separation and purification of small molecule products.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with OER, an applied potential to drive plastic oxidation reaction and achieve a targeted current density shows a significant decrease, suggesting diminished energy contribution in the electrocatalytic system of plastic oxidation coupled with HER than water splitting system. 52 For example, Liu et al 53 compared the electricity consumption for the hydrogen production in the aforementioned systems and revealed that at a current density of 100 mA cm −2 , the plastic oxidation coupled with the HER system exhibited a markedly lower electricity consumption of 24.9 kWh kg −1 (H 2 ), half of that for conventional water splitting system. Plastic electrochemical oxidation reactions typically occur in alkaline environments, concurrently engaging various cathodic reduction reactions, such as the HER, carbon dioxide reduction reaction (CO 2 RR), and nitrate reduction reaction (NO − 3 RR).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, plastic oxidation is also emerging as an attractive alternative to OER with the advantages of less energy input and waste utilization. In comparison with OER, an applied potential to drive plastic oxidation reaction and achieve a targeted current density shows a significant decrease, suggesting diminished energy contribution in the electrocatalytic system of plastic oxidation coupled with HER than water splitting system 52 . For example, Liu et al 53 .…”
Section: Introductionmentioning
confidence: 99%